Pengembangan Batik Desa Sidorejo dengan Metode Tye Die - Visnhu, Bartolomeus Galih (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Kuliah Kerja Nyata or known as KKN is an activity aimed at providing students with experience in the fields of science, art, and technology which also become a mandatory program for Atma Jaya Yogyakarta students. The implementation of KKN 80 was carried out from October to November 2021 using the KKN Society 5.0 model where the execution was conducted online considering the Covid-19 pandemic conditions. The KKN 80 Unit R group 87 located in Sidorejo village, Lendah District, Kulon Progo. Generally, the village has two main economic potentials in the form of agriculture and culture. Based on the result of observations, Sidorejo Village has the uniqueness of batik in the form of a figure eight which resembles the typical food of Geblek Renteng where this craft has the potential to be developed. However, the data shows that there are still a lot of people who do not have jobs. Therefore, the purpose of implementing KKN by group 87 is to provide job opportunities as well as assist in the development of batik types in Sidorejo Village. The preparation of the KKN report was done by collecting secondary data by searching for literature that was in accordance with the project as a reference for working on the report. The resulting output is a mapping of potential of the village, which is then made to be e-books, pocket books, and videos. Those output will explain related to village and its potential as well as the implementation of the development of batik in Sidorejo Village.